G-jitter mixer convection adjacent to a vertical stretching sheet - Sharidan, S.; Amin, N.; Pop, Ioan (Springer Netherlands, 2007)
This paper studies the effect of periodical gravity modulation, or g-jitter induced mixed convection, on the flow and heat transfer characteristics associated with a stretching vertical surface in a viscous and incompressible fluid. The velocity and temperature of the sheet are assumed to vary linearly withx, wherex is the distance along the sheet. It is assumed that the gravity vector modulation is given byg*(t)=go [1+? cos(p?t)]k, and the resulting non-similar boundary layer equations are solved numerically using an implicit finite-difference scheme. The effects of the amplitude of modulation, frequency of the single-harmonic component of oscillation, mixed convection parameter and Prandtl number on the skin friction and Nusselt number are discussed in detail.